Programming Arduino: getting started with sketches - Monk, Simon (McGraw-Hill's AccessEngineering, 2012)
"Using clear, easy-to-follow examples, Programming Arduino: Getting Started with Sketches reveals the software side of Arduino and explains how to write well-crafted sketches using the modified C language of Arduino. No prior programming experience is required! The downloadable sample programs featured in the book can be used as-is or modified to suit your purposes. - Understand Arduino hardware fundamentals - Install the software, power it up, and upload your first sketch - Learn C language basics - Write functions in Arduino sketches - Structure data using arrays and strings - Use Arduino's digital and analog inputs and outputs in your programs - Work with the Standard Arduino Library - Write sketches that can store data - Program LCD displays - Use an Ethernet shield to enable Arduino to function as a web server - Write your own Arduino libraries".